Impact of tropical land-use change on soil organic carbon stocks - a meta-analysis - DON, AXEL; SCHUMACHER, JENS; FREIBAUER, ANNETTE (Global change biology, 2011)
Land-use changes are the second largest source of human-induced greenhouse gas emission, mainly due to deforestation in the tropics and subtropics. CO₂ emissions result from biomass and soil organic carbon (SOC) losses and may be offset with afforestation programs. However, the effect of land-use changes on SOC is poorly quantified due to insufficient data quality (only SOC concentrations and no SOC stocks, shallow sampling depth) and representativeness. In a global meta-analysis, 385 studies on land-use change in the tropics were explored to estimate the SOC stock changes for all major land-use change types. The highest SOC losses were caused by conversion of primary forest into cropland (−25%) and perennial crops (−30%) but forest conversion into grassland also reduced SOC stocks by 12%. Secondary forests stored less SOC than primary forests (−9%) underlining the importance of primary forests for C stores. SOC losses are partly reversible if agricultural land is afforested (+29%) or under cropland fallow (+32%) and with cropland conversion into grassland (+26%). Data on soil bulk density are critical in order to estimate SOC stock changes because (i) the bulk density changes with land-use and needs to be accounted for when calculating SOC stocks and (ii) soil sample mass has to be corrected for bulk density changes in order to compare land-use types on the same basis of soil mass. Without soil mass correction, land-use change effects would have been underestimated by 28%. Land-use change impact on SOC was not restricted to the surface soil, but relative changes were equally high in the subsoil, stressing the importance of sufficiently deep sampling.